2017
DOI: 10.1093/jxb/erx102
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily distinct strategies for the acquisition of inorganic carbon from seawater in marine diatoms

Abstract: The uptake of dissolved inorganic carbon by marine diatoms is facilitated by solute carrier transporters or external carbonic anhydrases. The occurrence of these distinct strategies is unrelated to phylogeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 59 publications
5
19
0
1
Order By: Relevance
“…, Tsuji et al. ). The catalytic rate of CAs has been suggested to be generally pH‐dependent, and the maximal k cat of the enzymes are achieved under alkaline conditions (Xu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Tsuji et al. ). The catalytic rate of CAs has been suggested to be generally pH‐dependent, and the maximal k cat of the enzymes are achieved under alkaline conditions (Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…They are enzymes that catalyze the conversion of HCO 3 À to CO 2 at the cell surface and thus play a critical role in supplying Ci for photosynthesis (Moroney et al 2011, Hopkinson et al 2013). Among the three species studied here, there is currently no molecular evidence for eCAs in Phaeodactylum tricornutum , Samukawa et al 2014; Thalassiosira pseudonana contains eCAs (i.e., dCA1 and fCA1) located at the periplasmic space outside the cells and serve to convert HCO 3 À to CO 2 to facilitate the usage of HCO 3 À , Samukawa et al 2014; although Chaetoceros muelleri expresses eCA, these do not seem to play a primary role in Ci acquisition (Shen and Hopkinson 2015, Smith-Harding et al 2017, Tsuji et al 2017. The catalytic rate of CAs has been suggested to be generally pH-dependent, and the maximal k cat of the enzymes are achieved under alkaline conditions (Xu et al 2008, de Araujo et al 2014.…”
mentioning
confidence: 89%
“…Some diatoms also possess extracellular carbonic anhydrase (CA), which allows the rapid formation of CO 2 from abundant HCO 3 − in the periplasmic space and may provide cells a nearly unlimited supply of CO 2 (Martin and Tortell, 2008;Hopkinson et al, 2011;Samukawa et al, 2014). Tsuji et al (2017) demonstrated that some evolutionarily distant marine diatoms mainly take up CO 2 formed from HCO 3 − by external CA. However, the mechanisms that support the efficient movement of CO 2 across the plasma membrane and four-layered membranes of secondary plastids have yet to be clarified.…”
mentioning
confidence: 99%
“…Similarly, a recent study by Tsuji et al. () found no impact of AZ on the K 0.5 C i or V max for photosynthetic O 2 evolution in air‐bubbled cultures of C. muelleri . Together, these findings suggest that CA ext ‐mediated uptake of C i is only induced at very low CO 2 concentrations in this species.…”
Section: Discussionmentioning
confidence: 62%